1999
DOI: 10.1074/jbc.274.11.7441
|View full text |Cite
|
Sign up to set email alerts
|

Prophenoloxidase-activating Enzyme of the Silkworm, Bombyx mori

Abstract: Prophenoloxidase-activating enzyme (PPAE) was purified to homogeneity as judged by SDS-polyacrylamide gel electrophoresis from larval cuticles of the silkworm, Bombyx mori. The purified PPAE preparation was shown to be a mixture of the isozymes of PPAE (PPAE-I and PPAE-II), which were eluted at different retention times in reversed-phase high performance liquid chromatography. PPAE-I and PPAE-II seemed to be post translationally modified isozymes and/or allelic variants. Both PPAE isozymes were proteins compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
145
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(153 citation statements)
references
References 61 publications
6
145
1
1
Order By: Relevance
“…ProPO-activating Enzyme (PPAE)-Crude PPAE preparation referred to as PPAE (AS-salt) and purified PPAE preparation were obtained from larval cuticles of silkworms as previously reported (14).…”
Section: Methodsmentioning
confidence: 99%
“…ProPO-activating Enzyme (PPAE)-Crude PPAE preparation referred to as PPAE (AS-salt) and purified PPAE preparation were obtained from larval cuticles of silkworms as previously reported (14).…”
Section: Methodsmentioning
confidence: 99%
“…The soluble proteins of plasma, hemocyte lysate, and fat body were precipitated with trichloroacetic acid and subjected to SDS-PAGE and then immunoblotting with affinity-purified Hd-PGRP-1 and Hd-PGRP-2 antibodies, respectively. Previously it was reported that insect proPO system induced the activation of serine protease zymogen to active serine protease during 1,3-␤-D-glucan-dependent proPO activation (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)30). To explore the existence of serine protease activity during 1,3-␤-D-glucan-specific proPO activation, we examined the amidase activity in the presence of 1,3-␤-D-glucan and Ca 2ϩ by using commercially available trypsin substrate, Boc-PheSer-Arg-MCA.…”
Section: 3-␤-d-glucan and Pgn Binding Assay-mentioning
confidence: 99%
“…This enzyme produces toxic compounds to microorganisms by oxidizing phenols to melanin, and it also participates in the sclerotization of the cuticle, which is vital for the survival of insects (18). Many reports have been published about the proPO of the invertebrate and its activation mechanism (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A key question regarding the proPO activation system is how pattern recognition molecules can induce activation of the system in response to microbial infection.…”
mentioning
confidence: 99%
“…Microbial carbohydrates such as LPS, PGN, or 1,3-D-␤-glucan will first react with pattern recognition proteins, which then will induce activation of several serine proteases within the proPO system (7)(8)(9)(10)(11)(12). It is known that one of the serine proteases in the cascade, which is named proPO-activating enzyme or factor, will cleave proPO to generate the active enzyme, phenoloxidase (PO) (13)(14)(15)(16). This enzyme can produce toxic compounds to microorganisms by oxidizing phenols to melanin, and it also participates in the sclerotization of the cuticle, which is vital for the survival of insects (17).…”
mentioning
confidence: 99%